Building a sustainable job-rich recovery (International Labour Organization GenevaCH, 2011)
Attempts to bring together current thinking on the real-economy factors driving the current and previous financial crises, while drawing on experiences from around the world and underlining the key lessons learned with a view to developing long-term strategies for a sustainable recovery.
Keywords: ECONOMIC RECESSION